The Development of Learning Module with Mobile Augmented Reality Based on 9E Learning Cycle to Improve Problem Solving Skills - Hakim, Arif Rahman; Asikin, Muhammad; Nurcahyono, Adi (Universitas Negeri Semarang, 2021)
The aim of this research is to produce a learning module with mobile augmented reality based on 9E Learning Cycle. This research is a type of research design. The development model used is ADDIE model which consists of five development phases namely analyze, design, development, implementation, and evaluation. The results of this study are learning modules that have been installed with QR-code and ModulAR apps that runs on the Android operating system. The results of validation get from experts’ reviewer that consist of 4 mathematics education lecturers and 3 mathematics teachers that showed the predicate of products was valid without revision for use. Then, the module and ModulAR apps has been implemented at SMPN 2 Mantup, Lamongan which involved 68 students who were divided into experimental and control classes. The module and ModulAR apps has received a practical predicate based on the analysis of the practicality questionnaire filled out by experimental class’s students. The use of learning modules with mobile augmented reality based on 9E Learning Cycle is also effective to improve problem solving skills. It can be seen from the average n-gain score obtained 61.10% which is include in the moderate category and the results of the independent-samples t test show that the average of problem solving skills improvement in the experimental class is significantly higher than the control class. The purpose of this research was to produce a learning module with mobile augmented reality based on 9E Learning Cycle. This type of research was a research design developed using the ADDIE development model with five development steps, namely analysis, design, development, implementation, and evaluation. The results of this study are the learning module and the ModulAR application that runs on the Android operating system. The results of expert validation consisting of 4 mathematics education lecturers and 3 SMP / MTs mathematics teachers showed a valid predicate without revision for 8 aspects of validity. The product developed has been implemented at SMPN 2 Mantup, Lamongan which involved 68 students who were divided into experimental and control classes. The product developed has received a practical predicate based on the analysis of the practicality questionnaire filled out by students in the experimental class. The use of learning modules with mobile augmented reality based on the 9E Learning Cycle is also effective in improving problem solving skills. This is based on the average n-gain score of 61.10% which is included in the intermediate category and the results of the comparative test show that the average increase in problem-solving abilities in the experimental class is higher than the control class.